1993
DOI: 10.1007/bf01972752
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of magnetic resonance imaging (MRI) and histopathology in rabbit models of osteoarthritis and immune arthritis

Abstract: Osteoarthritis was surgically induced in mature male Dutch Belted rabbits by sectioning the fibular collateral and sesamoid ligaments and removal of the anterior horn of the lateral meniscus. The site of surgical intervention was detectable by MRI. Histopathologic analysis revealed severe focal cartilage lesions on opposing surfaces of the tibia and femur. Histology of cartilage adjacent to the osteoarthritic lesions appeared normal. In another animal model, arthritis was induced by immunization against ovalbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…However, both water and lipids are eliminated during the histological procedure, the reduction of the cartilage thickness on MR imaging is believed to be due to dehydration. This apparent 'MR' reduction in cartilage has also been found in the literature in other animal models (O'Byrne et al 1993). The correlation between cartilage measurements made on MR imaging with those performed on anatomical sections remains unknown.…”
Section: Interpretation Of Knee Joint Mr Imagesmentioning
confidence: 54%
“…However, both water and lipids are eliminated during the histological procedure, the reduction of the cartilage thickness on MR imaging is believed to be due to dehydration. This apparent 'MR' reduction in cartilage has also been found in the literature in other animal models (O'Byrne et al 1993). The correlation between cartilage measurements made on MR imaging with those performed on anatomical sections remains unknown.…”
Section: Interpretation Of Knee Joint Mr Imagesmentioning
confidence: 54%
“…2) measured in unloaded histological sections. Loss of chondrocytes increases the matrix/cell (M/C) area ratio in this model [6]. (Fig.…”
Section: Referencesmentioning
confidence: 71%
“…Eight weeks post partial meniscectomy, knees were fixed in 10% neutralbuffered formalin and stained with safranin 0/fast green with a hematoxylin counterstain for histological scoring. Total cartilage 2 area (mm) of the lateral tibial condyle and matrix/cell (M/C) area ratio [5,6] in lateral femoral condyle were measured using a computer based morphometric system (BioScan Optimus, Edmonds WA 98020).…”
Section: Rabbit Model Of Osteoarthritismentioning
confidence: 99%
“…Thut et al [14], in a study using rabbits that had undergone both anterior cruciate ligament (ACL) transection and meniscectomy, showed that disease severity was worst for the femur. Additionally, O'Byrne et al [15], again using rabbits but with removed fibular collateral and sesamoid ligaments and partially removed lateral meniscus, observed a reduced tibio-femoral thickness. Braunstein et al [16], in a longitudinal study of ACL transected dogs, concluded that over a period of 3 years, chondrocytes may produce a joint surface capable of supporting load.…”
Section: Introductionmentioning
confidence: 97%